Stabilization of Refrigerated Avocado Pulp: Chemometrics-Assessed Antibrowning Allium and Brassica Extracts as Effective Lipid Oxidation Retardants - Bustos Shmidt, Mariela Cecilia (2017)
The effectiveness of Allium and Brassica extracts to inhibit the evolution of lipids oxidation in avocado pulp under refrigeration (storage at 4 °C) was studied. Onion, garlic, scallion, white cabbage, cauliflower, and Brussels sprouts extract were tested as preserving agents in refrigerated avocado pulp. Allium extracts promoted almost a 60% retention of the intrinsic anti-radical capacity of the pulps. Considering secondary oxidation effects, extinction coefficient at 270 nm shows that all treated pulps (except those with scallion addition) were acceptable at the 30th storage day (K270 < 0.22), but they were all significantly less oxidized than the untreated samples (K270 = 1.8) (P < 0.05). Garlic-treated avocado showed the highest antioxidant effectiveness, based on C=CH cis proportion (Icis = 108.3), while samples with white cabbage extract presented the highest C=CH trans (Itrans = 5.7) proportion after 30 days. The PCA method was discriminant enough since 83.6% of the variance was explained by the first two principal components, allowing the samples to be grouped according to storage time and extract type. This study confirmed that the addition of garlic, onion, and cauliflower extracts enhanced lipid antioxidant properties in refrigerated avocado pulps.